A proteome‐scale analysis of vertebrate protein amino acid occurrence: Thermoadaptation shows a correlation with protein solvation but less so with dynamics. Issue 1 (20th August 2022) - Li, Zhen‐Lu; Buck, Matthias
Abstract: Despite differences in behaviors and living conditions, vertebrate organisms share the great majority of proteins, often with subtle differences in amino acid sequence. Here, we present a simple way to analyze the difference in amino acid occurrence by comparing highly homologous proteins on a subproteome level between several vertebrate model organisms. Specifically, we use this method to identify a pattern of amino acid conservation as well as a shift in amino acid occurrence between homeotherms (warm‐blooded species) and poikilotherms (cold‐blooded species). Importantly, this general analysis and a specific example further establish a broad correlation, if not likely connection between the thermal adaptation of protein sequences and two of their physical features: on average a change in their protein dynamics and, even more strongly, in their solvation. For poikilotherms, such as frog and fish, the lower body temperature is expected to increase the protein–protein interaction due to a decrease in protein internal dynamics. In order to counteract the tendency for enhanced binding caused by low temperatures, poikilotherms enhance the solvation of their proteins by favoring polar amino acids. This feature appears to dominate over possible changes in dynamics for some proteins. The results suggest that a general trend for amino acid choice is part of the mechanism for thermoadaptation of vertebrate organisms at the molecular level.